Constitutionality of DPR-DPRD From Independent Candidates - P Puspaningrum; Imam Al Ghozali Wulukada (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Electing and being elected is the right of each citizen which is guaranteed by the constitution of the Republic of Indonesia. However General Elections policy only regulates Political Parties which become the participants of the election who have the rights to nominate the member of DPR-DPRD. This regulation obligates the citizens’ rights to associate to a Political Party and does not organize their rights of electing or being elected independently in a representative system. This article is trying to conduct a study to the theory, principle and norms on the Representative system and also examining the principal assumption of UUD 1945 (the Constitution of 1945) related to the potency of independent candidates in the DPR-DPRD elections, elaborating the constitutional, juridical, political, and cultural obstacles to an independent candidate in the contestation of legislative election. By using juridical, conceptual and comparative analytic approaches, then this study results in a recommendation on two efforts of political supremacy through constitutional amendment or legal supremacy effort through judicial review of the Constitution of 1945 Article 22E paragraph (3) by relying on Article 28D paragraph (3) and Article 28 Junto Article 28E paragraph (3). Therefore, the election system of DPR-DPRD is carried out through two lines, political party line and independent line.